Anesthetic considerations of Joubert syndrome in patients with mitochondrial disease - A case report - - Jeong Yeon Kim; Koun Jeong; Ki Seob Han; Ji Eun Park; Mun Gyu Kim; Mi Roung Jun (Anesthesia and Pain Medicine, 2021)
Background Joubert syndrome and mitochondrial disease are rare congenital diseases in which a wide range of symptoms affects multiple organs. Patients with these diseases present characteristic symptoms related to the musculoskeletal, respiratory, and neurological systems, which make it difficult for anesthesiologists to manage the patient’s airway and choose appropriate anesthetic drugs. Case A 13-year-old male patient with Joubert syndrome and mitochondrial disease underwent elective surgery to insert a continuous ambulatory peritoneal dialysis catheter. Anesthesia was induced and maintained with propofol, remifentanil, and rocuronium. An I-gel was inserted to secure the airway; however, the fitting did not work properly, so the patient was intubated. The operation was completed without any major problems, and the intubated patient was transferred to the intensive care unit. Conclusions Anesthesiologists should determine the method of anesthesia and prepare for unintended complications based on a full understanding of these congenital diseases.